Identification of sectoral logistics service quality gaps by applying SERVQUAL method - Meidutė-Kavaliauskienė, Ieva; Vasilienė-Vasiliauskienė, Virgilija; Vasilis Vasiliauskas, Aidas (Transport, 2020)
Today, simply delivering a product to the right place at the right time is no longer enough. Customers demand more; they demand the full suite of logistics services. Customers thus seek higher-value and additional services, and more, which enable them to compete. Thus, the problem underlying analysis is customers’ growing dissatisfaction with existing services and their quality. Quality of service no longer gives business entities a competitive edge. It is vital for companies to have different activities, to operate in different branches of the economy, and to work with different types of goods. However, despite these differences, they all want to obtain maximum satisfaction from logistics services. With this in mind, the purpose of this article is to present a study examining the impact of logistics service quality on the satisfaction of companies working with different categories of goods Results indicated that different logistics service users do not have the same requirements for logistics service quality. Moreover, it was proved that SERVQUAL method is suitable for identification of sectoral value gaps, which can be applied in practice assuring competitive advantage.